A discourse analysis of airline job advertisements / Tan Chuin Hwa - Tan, Chuin Hwa (2019)
Researches and analysis have been done to look into the service, consumer satisfactions and marketing success in the aviation industry. This research draws inspiration from the lack of research done in aviation job advertisement industry. 10 selected cabin crew job advertisements from the Asia and non-Asia based Low Cost Carrier airlines will be analysed visually and textually. Using Kress and van Leeuwen’s Visual Grammar (2006) framework, the images and textual within the advertisements will be analysed to determine the representation of cabin crews. The findings from the research show that non-Asia based airlines focus more on branding the cabin crews with a sense of professionalism through their physical appearances, whereas the Asia based airlines focus more on educational background of the cabin crews. With the findings, it is hope to provide more language related insights to concerned parties as well as to help job advertiser to further understand the effectiveness of their advertisement. It is also hope to facilitate viewers to understand the intended message better.